Analysis of serum level of HE4 and CA125 considering selected risk factors among patients with endometrioid endometrial cancer - Abdalla, Nabil; Piorkowski, Robert; Slomka, Anna; Kania, Malgorzata; Sawicki, Wlodzimierz; Cendrowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2016)
The aim of the study : To assess the difference of serum level of HE4 and CA125 among patients with endometrioid endometrial cancer, considering the presence or absence of selected risk factors. Material and methods: A retrospective study of 46 patients, whose serum level of HE4 and CA125 level was documented, admitted to our Clinic because of endometrioid endometrial cancer. The statistical difference of both markers was analyzed considering certain risk factors. Results : In the examined group of patients there was no significant statistical difference of HE4 and CA125 levels among patients with and without the following risk factors: older age, menopausal status, overweight and obesity, hypertension, diabetes, early menarche, and family history of certain cancers. Similar results were obtained within the subgroup of patients with stage I endometrial cancer. Both HE4 and CA125 were significantly higher in premenopausal patients than in those after menopause in the more advanced stages of the disease. The same results were obtained within group of patients with advanced histological grading G2 and G3. In this group, higher levels of CA125 were observed among patients without hypertension. Among patients with histological grade G1 the serum level of HE4 was higher in the group of patients older than 60 years than it was in younger patients. Conclusions : In the examined group of patients serum levels of tumour markers may not be affected by the selected risk factors. Higher HE4 and CA125 levels among premenopausal patients may be an alarming sign of advanced stages and classes of histological grading.